2016
DOI: 10.2337/db15-1094
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Betaine Supplementation Increases Fgf21 Levels to Improve Glucose Homeostasis and Reduce Hepatic Lipid Accumulation in Mice

Abstract: Identifying markers of human insulin resistance may permit development of new approaches for treatment and prevention of type 2 diabetes. To this end, we analyzed the fasting plasma metabolome in metabolically characterized human volunteers across a spectrum of insulin resistance. We demonstrate that plasma betaine levels are reduced in insulin-resistant humans and correlate closely with insulin sensitivity. Moreover, betaine administration to mice with diet-induced obesity prevents the development of impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 57 publications
6
69
1
Order By: Relevance
“…Recently, a study demonstrated that white pitaya (Hylocereus undatus) juice attenuated insulin resistance and hepatic steatosis in HFD-induced obese mice and this effect was associated with increased expression levels of Fgf21-related genes [59] . White pitaya juice is rich in various polyphenols, flavonoids, and vitamin C. Furthermore, dietary betaine supplementation has also been shown to increase plasma Fgf21 levels and is associated with improved glucose disposal and reduced hepatic steatosis in HFD-fed mice [60] . Although Fgf21 was shown to exert a beneficial metabolic effect, in murine and human subjects with obesity or IR, serum Fgf21 levels were found to be elevated.…”
Section: Dietary Polyphenols Regulate Hepatic Fgf21 Expression and Cumentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study demonstrated that white pitaya (Hylocereus undatus) juice attenuated insulin resistance and hepatic steatosis in HFD-induced obese mice and this effect was associated with increased expression levels of Fgf21-related genes [59] . White pitaya juice is rich in various polyphenols, flavonoids, and vitamin C. Furthermore, dietary betaine supplementation has also been shown to increase plasma Fgf21 levels and is associated with improved glucose disposal and reduced hepatic steatosis in HFD-fed mice [60] . Although Fgf21 was shown to exert a beneficial metabolic effect, in murine and human subjects with obesity or IR, serum Fgf21 levels were found to be elevated.…”
Section: Dietary Polyphenols Regulate Hepatic Fgf21 Expression and Cumentioning
confidence: 99%
“…The stimulation of hepatic Fgf21 expression has been shown with curcumin, two other dietary polyphenols [36,57,58] , and white pitaya or dietary betaine supplementation [59,60] . It is necessary to determine whether ChREBP expression can be regulated by anthocyanin, resveratrol, and other dietary polyphenols.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…This study demonstrates that betaine attenuates ROS production, and subsequently suppresses VEGFR-2 signaling pathway and VEGF production. Dietary betaine supplementation has been shown to increase fibroblast growth factor (FGF)21 levels, to improve glucose homeostasis, and to reduce the hepatic lipid accumulation in mice [96]. Betaine plasma levels in humans are reduced in insulin-resistant conditions, and correlate closely with insulin sensitivity.…”
Section: Betaine and Hyperglycemia-induced Vascular Damagementioning
confidence: 99%
“…Among other effects, plasma betaine levels in humans are inversely linked to triglycerides and non-high density lipoprotein (non-HDL) cholesterol, and positively to HDL cholesterol. 16 …”
Section: Discussionmentioning
confidence: 99%
“…15 Plasma betaine levels are reported to be reduced in insulin-resistant subjects and to closely correlate with insulin sensitivity. 16 Moreover, stachydrine, the betaine of proline very abundant in citrus juice, which differs from GabaBet for its cyclic structure, 17 has been demonstrated to counteract the hGluc induced endothelial cell senescence via SIRT1 downregulation. 18 Another betaine, the 2-mercapto histidine betaine (ESH), namely ergothioneine, also protects EC against the hGluc induced endothelial senescence via the regulation of SIRT1/SIRT6 expression and their cellular targets, NF-κB and p66…”
Section: Introductionmentioning
confidence: 99%